Contrast-enhanced T1-weighted three-dimensional gradient-echo MR imaging of the whole spine for intradural tumor dissemination. - Sugahara, T; Korogi, Y; Hirai, T; Shigematu, Y; Ushio, Y; Takahashi, M (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE When evaluating intradural tumor dissemination in the spine, contrast-enhanced T1-weighted 2D spin-echo (2D-SE) images are frequently problematic because most of the lesions are very small. Our purpose was to compare 2D-SE images with 3D gradient-echo (3D-GE) postcontrast images to determine which technique is better for depicting intradural tumor dissemination.METHODS Ten patients with and 10 without intradural tumor dissemination were examined prospectively with MR imaging. After contrast administration, all patients underwent sagittal imaging with 2D-SE and 3D-GE sequences. Subsequently, the 2D-SE, 3D-GE, and multiplanar reconstruction (MPR) images of the 3D-GE sequence were evaluated for image quality, lesion detectability, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR) of the disseminated lesions.RESULTS Although delineation of spinal cord from CSF was slightly poorer on the 3D-GE sequences than on the 2D-SE sequences, the difference was not significant. In the evaluation of image artifacts and contrast between spinal cord and CSF, there was no significant difference. In seven patients with nodular enhancement, the 3D-GE sequence detected 46 lesions and the 2D-SE sequence detected 36. With MPR, the greatest number of lesions (n = 51) was detected, and vascular enhancement was clearly distinguished. There was no difference in SNR and CNR of lesions between the 3D-GE and 2D-SE sequences.CONCLUSION The contrast-enhanced 3D-GE technique offers advantages over 2D-SE imaging in detecting intradural tumor dissemination, especially when the MPR technique is applied. This technique should be used for detecting intradural tumor dissemination.